Delivering healthcare in multiprofessional teams: the negotiation of tasks. - Tremblett, Madeleine; Smart, Cordet; Auburn, Tim (Journal of Integrated Care, 2025)
Purpose: Multiprofessional team working is assumed to be difficult. This is often associated with professional identity and jurisdiction. Despite anticipated difficulties, few studies examine teams working in their main arena: team meetings. One important function of these multiprofessional team meetings is to determine future tasks and next steps for patients. This paper examines the negotiation between professionals of what these next steps should be. Design/methodology/approach: Data was collected in 2018 and 2019, from three Community Learning Disability Teams in the UK, with a total length of 12 h and 37 min. Conversation analysis (CA) was used to analyse 22 extracts, at points in the interactions when there were negotiations on the next steps the team should take for clients. Findings: Negotiations were characterised by propositions and counter propositions. They occurred when a course of action was proposed that made a specific professional's role relevant, which were then countered by that professional. Countering was achieved by professionals separating themselves from the team, using first-person pronouns and making statements on their next steps. In both propositions and counters professionals orient to epistemics and deontics, important for how their turns-at-talk were receipted by other team members. Originality/value: This paper shows that instead of problematic, professional identity was used as a conversational resource. Negotiations are key for multiprofessional teams to determine optimal next steps for patients, and who could and should do specific tasks. Professionals orient to knowledge of professional identity to propose tasks that others could do, and to counter these propositions.